Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
How do i work this equation out?
(2x-1)^2 -6 = 30
could you explain how you went from the starting equation to: 4x^2 -4x +6=30
where did the -4x come from?
Thnx :)
3 Answers
- Anonymous10 years agoFavorite Answer
(2x-1)^2 -6 = 30
4x^2 - 4x +1 -6=30
4x^2-4x-5=30
4x^2-4x=35
4x^2-4x-35=0
- BeeLiz19Lv 710 years ago
assuming equation is
2(x-1)^2 - 6 = 30
2(x-1)^2 = 30 + 6
2(x-1)^2 = 36
now divide both sides by 2
2(x-1)^2 / 2 = 36/2
(x-1)^2 = 18
take the square root of both sides:
√(x-1)^2 = +/- √18
x - 1 = +/- (√9x2)
x = 1 +/- (√9 x √2)
x = 1 +/- 3√2
can't simplify further, plug into calculator for numerical value.
NOTE: you said "work this equation out", that typically means solve!!!!!!!!!!!!!!
If you meant: Expand the brackets and collect like terms, that's different!!!!!
assuming THAT is what you meant:
(2x-1)^2 - 6 = 30
(2x-1)(2x-1) - 6 - 30 = 0
2x(2x) + 2x(-1) -1(2x) -1(-1) - 36 = 0
4x^2 - 2x - 2x + 1 - 36 = 0
4x^2 -4x - 35 = 0
- ?Lv 710 years ago
Continuing and building on ?'s work,
4*x^2 - 4*x - 35 = 0
(2*x + 5)*(2*x - 7) = 0
2*x = - 5 or 2*x = 7
x = -5/2 or x = 7/2 <<<